2008
DOI: 10.1007/s11627-008-9163-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a DRE-binding transcription factor from Medicago truncatula by deleting a Ser/Thr-rich region

Abstract: We isolated a DREB homologue gene, MtDREB2A, from Medicago truncatula. Its deduced protein contains an AP2 domain of 59 amino acids. The expression of MtDREB2A was significantly induced in roots by salt and drought treatments. Using megaprimer PCR, we deleted a Ser/ Thr-rich coding region between residues 142 and 190, and transformed MtDREB2A to a constitutive form, namely, MtDREB2a. Yeast one-hybrid assay revealed that both MtDREB2A and MtDREB2a specifically bound to the dehydration-responsive element (DRE) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…However, the regulatory mechanism of stability by NRD is not clear. Whether this posttranslational regulation is common among other plant species is also unclear, although the removal of a region that corresponds to the DREB2A NRD from MtDREB2A of Medicago truncatula enhanced activity in yeast (Saccharomyces cerevisiae; Chen et al, 2009a).…”
mentioning
confidence: 99%
“…However, the regulatory mechanism of stability by NRD is not clear. Whether this posttranslational regulation is common among other plant species is also unclear, although the removal of a region that corresponds to the DREB2A NRD from MtDREB2A of Medicago truncatula enhanced activity in yeast (Saccharomyces cerevisiae; Chen et al, 2009a).…”
mentioning
confidence: 99%
“…In our previous study, we isolated a MtDREB2A gene and identified a regulatory domain (central part of MtDREB2A) in the regulation of DREB2A (Chen et al 2009a). In this study, we isolated and characterized a DREB gene from M. truncatula (MtDREB1C), which was a cold-acclimation-specific gene (Pennycooke et al 2008) exhibiting the highest homology to Arabidopsis DREB1C gene.…”
Section: Discussionmentioning
confidence: 99%
“…The function of downstream genes controlled by MtDREB1C associated with freezing stress tolerance in the transgenic China Rose should also be further studied. Although only one surviving line has been obtained and the homolog of DREB in China Rose plants has yet to be identified, we may hypothesize that the China Rose might possess a DER-DREB-based stress response system similar to that in Arabidopsis (Liu et al 1998), rice (Oh et al 2005), wheat (Shen et al 2003a), and Medicago (Chen et al 2009a). With this knowledge, DREBtransformed China Rose lines with higher freezing-tolerance will be obtained in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations